Pengaruh Kedisiplinan Guru dan Motivasi Belajar Siswa terhadap Peningkatan Prestasi Belajar Siswa di MI se-Kecamatan Wonodadi Kabupaten Blitar - Khoiruzzaim Kurniawan (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2018)
The research in this thesis prompted by the weakening of discipline teachers who could be seen among others, it can be seen from teachers who skip their class/ default teacher, teachers who late go to the class or school, teachers who have no learning or incomplete preparation and also the low student motivation.. So the researcher wanted to examine the influence of the discipline of teachers and students' motivation to improve students` achievement in the school. The research method used in this research was quantitative in particularly survey research. As for the population in this research were all Elementary School (MI) students throughout Wonodadi sub-district, 18 schools. By using cluster sampling method, four schools were selected, consisting of 2638 students and 229 teachers. In this research, the number of samples was based on the table of samples determining number from specific populations developed by Issac and Michael by using standard error of 5% in a number of 307 students and 135 teachers. Data was collected by questionnaire instrument. Data analysis and hypothesis testing in this research used simple regression, multiple regression. The results showed that (1) There was a positive and significant influence between the discipline and student achievement in Islamic Elementary School (MI) student achievement throughout Wonodadi sub-district. (2) There was a positive and significant influence between learning motivation on student achievement (3) There was a positive and significant influence between discipline and learning motivation on student achievement